2011
DOI: 10.1155/2011/949302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Clover Isoflavones over Skin, Appendages, and Mucosal Status in Postmenopausal Women

Abstract: Objective. Evaluate in postmenopausal women the effect of red clover extract (RCE) isoflavones over subjective status of skin, appendages, and several mucosal sites. Method. Postmenopausal women (n = 109) were randomly assigned to receive either two daily capsules of the active compound (80 mg RCE, Group A) or placebo of equal appearance (Group B) for a 90-day period. After a washout period of 7 days, medication was crossed over and taken for 90 days more. Subjective improvement of skin, appendages, and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
(59 reference statements)
0
15
0
9
Order By: Relevance
“…Currently, extracts of red clover are available as dietary supplements, recommended as an alternative to the conventional hormone replacement therapy. On the other hand, clinical data collected in the previous review provided disputable results concerning the efficacy of red clover isoflavone administration (Table ) . Moreover, the bioavailability of clover‐derived substances and the possibility of their interactions with other medications are only partly elucidated.…”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently, extracts of red clover are available as dietary supplements, recommended as an alternative to the conventional hormone replacement therapy. On the other hand, clinical data collected in the previous review provided disputable results concerning the efficacy of red clover isoflavone administration (Table ) . Moreover, the bioavailability of clover‐derived substances and the possibility of their interactions with other medications are only partly elucidated.…”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 98%
“…On the other hand, clinical data collected in the previous review [1] provided disputable results concerning the efficacy of red clover isoflavone administration (Table 4). [62][63][64][65] Moreover, the bioavailability of clover-derived substances and the possibility of their interactions with other medications are only partly elucidated. Results providing some new information about bioavailability of red clover isoflavones in humans were published by Lipovac and co-authors in 2015.…”
Section: Trifolium Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Red clover has good safety profile, no significant side effects are mentioned in studied literature. [14] Analysis of the menopause rating scale in the present study showed that both the groups were comparable regarding the reduction of menopause rating scale and there was no statistically [15] In another study done by Ehsanpour et al, a total of 55 women completed the study, 28 subjects in red clover and 27 in placebo group. Mean score of total quality of life (p < 0.001 in both groups), mean score of quality of life in vasomotor domain (p < 0.001 in both groups), psycho-social domain (p < 0.001 in red clover and p = 0.02 in placebo group) and physical domain (p < 0.001 red clover and p = 0.01 placebo group) significantly reduced compared to the baseline values.…”
Section: Discussionmentioning
confidence: 58%
“…[29] Red clover F (113) ↑ Estrogen levels and benefits to specific organs or systems. [30] Low-energy diet and low-fat, high-protein diet M (31) Diet ↑ testosterone and improves sexual function.…”
Section: Ginger (Mondia Whitei)mentioning
confidence: 99%